Improving tax compliance via tax education - Malaysian experience / Norzilah Hassan, Anuar Nawawi and Ahmad Saiful Azlin Puteh Salin - Hassan, Norzilah; Nawawi, Anuar; Puteh Salin, Ahmad Saiful Azlin (Universiti Teknologi MARA Cawangan Selangor, 2016)
Tax education has always been one of central focus to the tax authority in Malaysia. It reflects the commitment of the agency to educate taxpayer in every possible ways. The objective of this study is to determine whether tax education program tax implemented by the tax authority does effect the compliance among the taxpayers. The sample was randomly selected from population with 60 responses. It was found that taxpayers really used the information on tax education wisely. Although it still need some improvement, it is still the best practise to encourage more people to know and learn about tax. It also shows that the taxpayers have a good perception toward tax education programmed. For future research, this study suggests the positive perception towards tax education programmed of the taxpayer need to be enhanced to give the taxpayers more exposure on tax education programme.